Grounded theory as a methodology for exploring marketing strategies for a special context - Shivany, S.; Velnampy, T. (The International Journal Research Publication, 2015)
Research methodology means, how the research should be undertaken or it is theory or science of methods. Qualitative research refers to interpretative naturalistic approach to the world in which the study of things of in their natural settings, make sense of interpreting , phenomena, in terms of meaning people bring to phenomena. The outcome of the qualitative research is qualitative understanding of phenomena or experiential knowledge about the phenomena. Grounded theory approach although traditionally associated with sociology, nursing and health, and organizational studies. Grounded theory has, in recent years, started to enter the repertoire of marketing and consumer research. However, in comparison to other qualitative methodologies its application is still fairly confined to experiential consumer behavior, despite its potential for theoretical developments across a range of marketing phenomenon that are predicated on a behavioral component. Post war marketing environment is unique in its characteristics, understanding the in-depth, Un- known knowledge in that particular context is needy in the current research gap. Grounded theory grounds theories from the data to make known theories for generating new knowledge still there are lack of researches, which focused to generate theory in the post war marketing environment by using the grounded theory methodology. This study fills the gap by exploring the aptness of grounded theory methodology in exploring marketing strategy in the post war marketing environment.
Keywords: Grounded theory; Marketing strategy; Post war marketing environment